Direct And Indirect Speech Genre Gratitude’s (Journal of Pedagogical Inventions and Practices, 2022)
firstly, it is due to the fact that it is carried out within the framework of the anthropological direction, including semantic-pragmatic and cognitive analysis. Secondly, genre studies is currently in the focus of modern linguistics. Thirdly, it should be emphasized that the study of the speech genre of gratitude, which has not yet been the subject of special research, is relevant for Russian studies at the beginning of the XXI century in connection with the specifics of the socio-cultural environment in modern Russia.